From Heterolytic to Homolytic H2 Dissociation on Nanostructured MgO(001) Films As a Function of the Metal Support - Chen, Hsin-Yi Tiffany; Giordano, Livia; Pacchioni, Gianfranco (Journal of physical chemistry. C, 2013)
It is well-known that the H2 molecule dissociates heterolytically on stepped MgO surfaces with formation of protons bound to O2– anions (OH groups) and hydride ions bound to Mg cations (MgH groups). Homolytic splitting, with formation of a pair of OH groups per adsorbed H2 molecule, is only possible in special conditions, like for polar MgO(111) surfaces or under irradiation due to the generation of O– radicals. In this work, we demonstrate, based on first-principles DFT calculations, that homolytic splitting of H2 is the thermodynamically most favored dissociation mode if MgO(001) films of a few atomic layers are deposited on a metal support. The choice of the support is crucial. In fact, on MgO/Ag(001) ultrathin films, H2 dissociation resembles the behavior of the bare MgO surface, while on MgO/Au(001), homolytic dissociation is preferred. The reason lies in the different position of the Fermi level in the two metal/oxide interfaces. The lower Fermi level (higher work function) of MgO/Au(001) favors the transfer of the H2 electrons to the metal support via electron tunneling through the ultrathin insulating layer (adsorption of protons). This is another manifestation of the unusual behavior of oxides at the nanoscale. It is of general relevance for the splitting and reactivity of covalently bound molecules.